2007
DOI: 10.1100/tsw.2007.139
|View full text |Cite
|
Sign up to set email alerts
|

Pea Seedling Histaminase as a Novel Therapeutic Approach to Anaphylactic and Inflammatory Disorders

Abstract: Amine oxidases (AOs) are ubiquitous enzymes involved in the metabolism of biogenic amines. Copper AOs (Cu-AOs) catalyze the oxidative deamination of primary amine groups of several biogenic amines, such as putrescine, cadaverine, and histamine. In the present review, the effects of a plant amine oxidase (Cu-AO, histaminase, EC1.4.3.6) purified from pea seedlings in the modulation of IgE-mediated allergic reactions, and in the prevention of cardiac and splachnic postischemic reperfusion damage are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…It is worth highlighting that the DAO activity of both products showed minimal variation among different production batches. These results are in good agreement with previously published data indicating a higher catalytic turnover rate for plant-than animal-derived DAO [5,23,37].…”
Section: Suitability Of the Methods For The Determination Of Dao Activsupporting
confidence: 93%
See 1 more Smart Citation
“…It is worth highlighting that the DAO activity of both products showed minimal variation among different production batches. These results are in good agreement with previously published data indicating a higher catalytic turnover rate for plant-than animal-derived DAO [5,23,37].…”
Section: Suitability Of the Methods For The Determination Of Dao Activsupporting
confidence: 93%
“…DAO (EC 1. 4.3.22), which belongs to the category of copper-containing amine oxidases, is a homodimeric and ubiquitous enzyme found in microorganisms, plants and animals, generally in the range of 140 to 200 kDa [4][5][6][7][8]. In particular, DAO catalyzes the oxidative deamination of the primary amino group of histamine to imidazole acetaldehyde, consuming dioxygen with the concomitant release of stoichiometric amounts of ammonia and hydrogen peroxide ( Figure 1) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A higher catalytic capacity of DAO enzymes of plant origin in degrading certain amino substrates has been described by some authors in comparison with those of animal origin [ 129 , 135 , 136 , 137 ]. Specifically, the germinated sprouts of certain edible legumes have been pointed out as interesting sources of DAO enzyme.…”
Section: Histamine Intolerancementioning
confidence: 99%
“…Plant copper‐containing amines oxidases have been a point of interest in therapeutic studies because other copper oxidases such as ceruloplasmin and bovine serum amine oxidases have been shown to possess antioxidant , cardioprotective , and even antitumoral properties . It has also been suggested that pea seedling DAO can reveal an antioxidant‐like protection by reducing tissue damage induced by reactive oxygen species generated during the anaphylactic reaction . Furthermore, pea seedling DAO was found to counteract cardiac anaphylaxis and pulmonary asthma‐like reaction to aerosolized allergens in sensitized guinea pigs by an antioxidant activity and inactivation of endogenously released histamine .…”
Section: Introductionmentioning
confidence: 99%